2022
DOI: 10.3390/dj10070115
|View full text |Cite
|
Sign up to set email alerts
|

Color Stability of Orthodontic Ceramic Brackets and Adhesives in Potentially Staining Beverages—In Vitro Study

Abstract: The aim of this study was to evaluate the color stability of esthetic ceramic brackets and adhesive samples after immersion in most commonly consumed beverages. A hundred ceramic brackets from five different manufacturers (Forestadent®, G&H®, GC, DynaFlex®, and American Orthodontics) and 120 samples of adhesives (3M™Transbond™ XT and American Orthodontics BracePaste® color change adhesive and BracePaste® adhesive) were immersed into four different solutions: coffee, Coca-Cola®, the vitamin drink Cedevita®,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…A significant correlation between root resorption and orthodontic force level was found in several systematic evaluations [25,35,38]. Several studies claim that there is only scant proof to back up this association [35,88,89]. Orthodontic treatment aims to correct malocclusions or misaligned teeth and jaws.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A significant correlation between root resorption and orthodontic force level was found in several systematic evaluations [25,35,38]. Several studies claim that there is only scant proof to back up this association [35,88,89]. Orthodontic treatment aims to correct malocclusions or misaligned teeth and jaws.…”
Section: Discussionmentioning
confidence: 99%
“…This is more common with certain types of appliances, and not all of them [87]. It is common for patients to experience some discomfort during orthodontic treatment, particularly in the days after braces are tightened [88]. However, if the pain is severe or persistent, it could be a sign of a more serious problem, such as a loose bracket or wire [88].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…18−20 As a result, all patients treated using ceramic or polymer-based brackets should reduce the consumption of staining foods and drinks to diminish the severity of this sequelae. 1,21 Therefore, bracket staining and assessment of color change was not part of this study objectives.…”
Section: Discussionmentioning
confidence: 99%
“…Figure 6 C highlights this trend by demonstrating that color variations detected (OPTB + 30% of NF_TiO 2 ) were numerically smaller and statistically significant (Δ E ab : p = 0.044, Δ E 00 : p = 0.014) compared with those from OPTB after 10,000 thermocycles. Šimunović et al [ 59 ], while investigating the color stability of orthodontic dental adhesive resins, indicated that degree of conversion, water sorption, polymer composition, temperature, and humidity impact the color stability of dental biomaterials through a complex and multifactorial process.…”
Section: Discussionmentioning
confidence: 99%